PENERAPAN RENCANA PELAKSANAAN PEMBELAJARAN AKIDAH AKHLAK BERBASIS KURIKULUM 2013 DI MTSN 5 BULUKUMBA - ., Usman; ., Muzakkir; ., Usman (Inspiratif Pendidikan, 2022)
The implementation of the implementation plan for learning morals based on the 2013 curriculum at MTsN 5 Bulukumba, that the reality of the preparation of the lesson plan (RPP) at MTsN 5 Bulukumba has been prepared independently by the subject teacher, the compenents of the lesson plan by the teacher at MTsN 5 Bulukumba are akidah akhlak lessons efer to the Minister of Education and Culture No. 22 of 2016 which includes the indentity of the lesson plans, indicators of competency achievement, learning objectives, learning marerials, learning resources and learning steps and learning assessments. The implementation of learning akidah akhlak on the 2013 curriculum at MTsN 5 Bulukumba has been in accordance with the instrument or compenent of the learning can be seen ini preliminary learning activities, core learning activities to closing learning activities. Constraints experienced by teachers of akidah akhlak subjects in the preparation of RPP based on the 2013 curriculum at MTsN 5 Bulukumba are that there are still teachers who lack understanding of the preparation of RPP, lack of facilities and infrastructure that suppot the preparation and implementation of RPP based on the 2013 curiiculum and the preparation of RPP takes a long time.